KAJIAN BIBLIOMETRIKA MAJALAH METALURGI LIPI - Rochani Nani Rahayu; Nurhayati Nurhayati (Perpustakaan Nasional RI, 2017)
This bibliometric study aims to find out: 1) The number of articles published in Metallurgy Magazine; 2) The language used in the articles; 3) The number of references used in the articles of Metallurgy Magazine; 4) The number and gender of the authors; 5) Collaboration of the authors and 6) Institu tions that participate in the writing of the articles. Results of the study obtained were as follows. 1) The number of articles published in Metallurgy Magazine was 130 titles, with the most title was 35 (26.93%) in 2014 and the least title was 19 (14.62%) in 2015. 2) Indonesian a1ticles amounted to 121 titles (93.07%) and English articles amounted to 9 titles (6.93%). 3) The total of references was 1500 titles, and the most was 14.13 references I article in 2013 and the least was 8.05 references I article in 2015. 4) Of the total of 317 authors, the number of male authors was 269 (84.86%) and female authors was 48 (15.14%). 5) The collaboration of two authors was in the first rank amounted to 44 articles (33.33%), the second was single authors amounted to 35 titles (26.92%), the third was the collaboration of three authors amounted to 25 titles (19.23%), and the collaboration of four or more authors noticeably amounted to 26 titles (20.52%). 6) The institution that contributed most articles was LIPI, followed by BATAN and the University of Indonesia. It was concluded that: 1) the number of articles per year was relatively constant with typically constant number of references; 2) it showed that Indonesian language was more widely used than English; 3) The number of male authors were more than that of female authors, and 4) the number of articles written by two authors was in the first rank; 5) research institutes did more contributions in Meta/urgi Magazine.